REFORMASI BIROKRASI POLRI DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK PADA KEPOLISIAN DAERAH SULAWESI SELATAN - Ridwan DP (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2018)
This research was conducted to: (1) Want to know what South Sulawesi Regional Police are doing in improving the quality of public services to achieve the target according to the Outcome Indicator; (2) Want to know what is done by the South Sulawesi Regional Police in an effort to improve the quality of service of the Indonesian National Police to be excellent; (3) Want to know what is done to improve the Capacity and Accountability of Performance of the South Sulawesi Regional Police. This research uses descriptive qualitative research method with a case study research strategy by taking a sample of 3 people in the service department, namely Integrated Police Service Centers (SPKT) as reporters (community), Traffic Unit (Sat Lantas) as applicants for Driving Permits (community) and Security Intelligence Unit (Sat Intelkam) as applicant for Police (community) Records. This research was conducted for 2 weeks, May 7-23. The results of this study indicate that: (1) the form of POLRI services that are perceived to be less fulfilling than the expectations of the community: (2) there is still a weak link between budget inputs and organizational performance and there is no comprehensive standardization of apparatus facilities and infrastructure: (3) the weak link between budget input and organizational performance, and activity orientation is still not fully focused on the expected results and the impact of the benefits caused to the public / public both directly and indirectly and the amount of operational costs that are not comparable to the quality of service or the resulting development impacts. However, in general, the South Sulawesi Regional Police is capable of implementing a good, clean and free from Corruption Collusion and Nepotism (KKN) governance, increasing the quality of public services and increasing the capacity and accountability of bureaucratic performance.